Food Policy Research Capacity Indicators (FPRCI), 2011-2018: 2019 Global Food Policy Report Annex Table 3 - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
Food policy research plays a crucial role in guiding the agricultural development of countries. To achieve food security goals, countries need to strengthen their capacity to conduct food policy research. Strong local policy research institutions help in shaping an evidence-based policy-making process. Measuring national capacity for food policy research is important for identifying capacity gaps in food policy research and guiding the allocation of resources to fill those gaps. Food policy research capacity is defined as any socioeconomic or policy-related research capacity in the area of food, agriculture, or natural resources. To measure this capacity, the International Food Policy Research Institute (IFPRI) developed a set of indicators of the quantity and quality of policy research at the country level. IFPRI created a database for food policy research capacity in 2010 and has continued to expand and refine it. The data presented are currently collected for 33 countries; data for Myanmar were added in 2017. A consistent methodology is followed to enable comparison of values across time and countries. The database was most recently updated with numbers for 2018. “Analysts/researchers” is a head count of professionals employed at local organizations whose work involves food policy research or analysis. To introduce some uniformity, IFPRI also presents a modified quantification of the headcount: "full-time equivalent analysts/researchers with the Ph.D. equivalent." To obtain an indicator of per capita food policy research capacity, this research capacity is then divided by the country’s rural population ("full-time equivalent researchers per million rural residents"). This helps to illustrate the impact of local food policy research in a country. This indicator was last updated in 2015. The quality of a country’s food policy research capacity is estimated by tallying the number of relevant international publications in peer-reviewed journals over a five-year period. IFPRI views this as a reflection of the local enabling environment for food policy research. This indicator allows for comparison across countries, as it ensures an internationally accepted standard of quality for publications. The final indicator ("publications per full-time equivalent researcher") is derived by dividing the number of international publications by the number of full-time equivalent researchers with a Ph.D., providing a measure of productivity.